Ginsenoside Rd protects transgenic Caenorhabditis elegans from β-amyloid toxicity by activating oxidative resistant - Mi, Lihan; Fan, Meiling; Liu, Tianjia; Wu, Donglu; Wang, Yang; Li, Fuqiang; Cai, Yong; Qiu, Zhidong; Liu, Da; Cao, Lingling (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a serious public health issue and few drugs currently available that only target the symptoms. It is well established that oxidative stress plays a crucial role in AD and there is compelling evidence linking oxidative stress to β-amyloid (Aβ). An exciting source of potential new AD therapeutic medication possibilities is medicinal plants. Ginsenoside Rd (GS-Rd) is one of the main bioactive substances in ginseng extracts. In our study, we used network pharmacology analysis to identify overlapping GS-Rd (therapeutic) and AD (disease)-relevant protein targets, gene ontology (GO) bio-process annotation and KEGG pathway analysis data predicted that GS-Rd impacts multiple targets and pathways, such as the MAPK signal pathway and the JAT-STAT3 signaling pathway. We then assessed the role of GS-Rd in C. elegans and found that GS-Rd prolongs lifespan, improves resistance to heat stress, delays physical paralysis and increase oxidative stress responses. Overall, these results suggest that GS-Rd protects against the toxicity of Aβ. RNA-seq analysis revealed that GS-Rd achieves its effects by regulating gene expression like daf-16 and skn-1, as well as by participating in many AD-related pathways like the MAPK signaling pathway. In addition, in CL4176 worms, GS-RD decreased reactive oxygen species (ROS) levels and increased SOD activity. Additional research with transgenic worms showed that GS-RD aided in the movement of DAF-16 from the cytoplasm to the nucleus. Taken together, the results indicate that GS-Rd significantly reduces Aβ aggregation by targeting MAPK signal pathway, induces nuclear translocation of DAF-16 to activates downstream signaling pathways, and increases resistance to oxidative stress in C. elegans in order to protect against Aβ-induced toxicity.